2013
DOI: 10.1108/bfj-10-2011-0274
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and utilization of starter cultures for the development of wheyghurt drink

Abstract: PurposeWhey products have conventionally been professed as a means of reducing ingredient costs. The authentic benefits of adding whey products are the enhanced worth resulting from flavor, texture and nutritional improvements as well as nutraceutical or health‐enhancing payback. Therefore, the present study aims to isolate and characterize suitable starter cultures for the production of wheyghurt drink.Design/methodology/approachKeeping in view all the benefits of yoghurt technology this study was planned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These authors analyzed the general appearance (graininess, visual roughness, serum separation, particle size, and rheological properties) and observed that the increase in whey concentration caused a decrease in graininess and visual roughness and an increase in serum separation and flow behavior index. On the other hand, Saeed et al (2013) selected strains of L. delbrueckii subsp. bulgaricus and S. thermophilus to produce a wheygurt (fermented whey using the yogurt starter culture) with acceptable characteristics.…”
Section: Fermented Drinksmentioning
confidence: 99%
“…These authors analyzed the general appearance (graininess, visual roughness, serum separation, particle size, and rheological properties) and observed that the increase in whey concentration caused a decrease in graininess and visual roughness and an increase in serum separation and flow behavior index. On the other hand, Saeed et al (2013) selected strains of L. delbrueckii subsp. bulgaricus and S. thermophilus to produce a wheygurt (fermented whey using the yogurt starter culture) with acceptable characteristics.…”
Section: Fermented Drinksmentioning
confidence: 99%
“…(2021) and Saeed et al. (2013) produced a whey–yogurt using selected strains of L. delbrueckii subsp. bulgaricus and S. thermophilus , which resulted in a stable and acceptable drinks using a 2% inoculum of the LAB starter culture.…”
Section: Advantages and Applications Of Whey Proteins In Food Industrymentioning
confidence: 99%
“…This prebiotic beverage exhibits strong antimicrobial properties against pathogenic strains, indicating its potential as a functional food or nutraceutical. In different contributions, El-Aidie, Elsayed, et al ( 2021) and Saeed et al (2013) produced a whey-yogurt using selected strains of L. delbrueckii subsp. bulgaricus and S. thermophilus, which resulted in a stable and acceptable drinks using a 2% inoculum of the LAB starter culture.…”
Section: Beverages and Fermented Drinksmentioning
confidence: 99%
“…Combinations of yoghurt-derived L. delbrueckii subsp. bulgaricus and S. thermophilus cultures were extensively tested for their capability to reduce the lactose content, and for the acidifying and proteolytic activities (Gallardo-Escamilla et al 2007;Pescuma et al 2008;Almeida et al 2009;Pescuma et al 2012;Saeed et al . 2013;Sohrabi et al .…”
Section: Lactic Fermented Whey Beveragesmentioning
confidence: 99%